On the Ecological Anthropology - Łastowski, Krzysztof (Anthropological Review, 1987)
An attempt to discuss the research tasks of ecological anthropology as a field of science exceeding the classical understanding of anthropology. The presented model of socio-cultural system places the subject of ecological anthropology on the border line between the biological and humanistic disciplines.